African passions and other stories - Rivera, Beatriz, 1957- (Arte Público Press, 2017)
Stories on strong Cuban women who live in a Hispanic barrio in Jersey City, pursuing love and wealth, frequently with rather weak men. An examination of Hispanic womanhood by a Cuban woman who emigrated to the U.S. at the age of three and has a university degree from the Sorbonne in Paris.